2008
DOI: 10.3846/1648-715x.2008.12.271-280
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Housing Market in Lithuania

Abstract: Cointegration and Granger causality tests were used for the statistical analyses of the housing market in Lithuania. The relationship between the cost of housing and afford‐ability on the one hand, and interest rates, GDP and average incomes on the other was not proven to exist using the given statistical methods. The period of increase in the cost of housing in Lithuania over the last five years is exceptional and difficult to explain using fundamental economic factors and their fluctuation trends alone. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Watkins and Merrill (2003) identify four stages in property market evolution and development: inactivity, cautious beginnings, hyper-growth, and seeking equilibrium. Analyzing residential real estate in Lithuania Ivanauskas et al (2008) analyzed a three-stage market development framework characterized by periods of 1992-2002, 2002-2005, and 2005-2006. Bearing this in mind, the evolution of the property market in Lithuania can be characterized by seven stages of its development (Table 2).…”
Section: Modeling Commercial Property Market Evolution In Lithuaniamentioning
confidence: 99%
“…Watkins and Merrill (2003) identify four stages in property market evolution and development: inactivity, cautious beginnings, hyper-growth, and seeking equilibrium. Analyzing residential real estate in Lithuania Ivanauskas et al (2008) analyzed a three-stage market development framework characterized by periods of 1992-2002, 2002-2005, and 2005-2006. Bearing this in mind, the evolution of the property market in Lithuania can be characterized by seven stages of its development (Table 2).…”
Section: Modeling Commercial Property Market Evolution In Lithuaniamentioning
confidence: 99%
“…-in construction industry and in real estate sector (Zavadskas 2008;Zavadskas et al 2007a;Zavadskas andAntuchevičienė 2006, 2007;Zavadskas and Kaklauskas 2008;Ivanauskas et al 2008;Kaklauskas et al 2009Kaklauskas et al , 2009aMickaitytė et al 2008;Rutkauskas et al 2008;Urbanavičienė et al 2009), -in energy sector (Štreimikienė 2007;Grundey 2008b;Klevas et al 2007Klevas et al , 2009Staniškienė and Šliogerienė 2009), -in the sector of transportation (Burinskiene 2009;Burinskiene et al 2009;Mačiulis et al 2009), -in tourism sector (Grundey 2008a; , as well as in other sectors of economy and social life. Summarizing the propositions, intended for the characteristics of the "power" concept, it is necessary to mention, that this concept may be treated as very useful when reacting to the challenges for the sustainable development, which arise under the contemporary conditions of the globalization and knowledge based society creation.…”
Section: Sustainable Development and Creation Of The Knowledge Based mentioning
confidence: 99%
“…Although Ivanauskas et al (2008) did not identify a causal relation between interest rate and housing prices, Leika and Valentinaitė (2007) showed that real interest rate and credit supply were significant determinants of housing prices.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…Still, Ivanauskas et al (2008) argued that neither GDP nor disposable income were causal determinants of housing prices in the period from 1998 to 2014. They explained that the negative results on the possible causality of housing costs and GDP might indicate a housing costs bubble.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
See 1 more Smart Citation